Analyzing Consumer Preferences in Selecting Halal Tourism Destination - Jalil, Nurhidayati Kasrul; Akbar, Nashr (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: This paper examines consumer behavior, specifically the Indonesian society's preference for making halal tourism in the Riau region a tourism destination.Design/Method/Approach: The methodology applied in this research is quantitative with the SEM-PLS approach. Sampling was done using purposive sampling method. The number of respondents involved was 256 people with an age range of 16 to 55 years old. This study adopts variables based on the Theory of Planned Behavior, which identifies three exogenous latent variables (É›), namely Attitude, Subjective Norm, and Perceived Behavioral Control. Meanwhile, the endogenous latent variable (Î·) in this research is the Preference for Halal Tourism.Findings: The results of this study revealed that the perceived behavioral control variable has the largest, positive, and significant influence.Originality/Values: The implications of this research can assist in the development of the halal tourism industry in Indonesia, particularly in the Riau region. Industry players and stakeholders can take steps and policies to enhance aspects such as subjective norms and perceived behavioral control to meet tourists' preferences. Academics can also contribute to advancing digital literacy, research, and innovation in the halal industry, thereby making a significant contribution to the dynamic and innovative digital ecosystem within the halal value chain.